Implementing the Kids’ Athletics Program in the System of Increasing the Level of Physical Performance of Youth - Ján Jakubík; Jaroslav Broďáni (Physical Education Theory and Methodology)
Objectives. The objective of this study was to verify the impact of the IAAF project “Kids’ Athletics” on the physical performance of pupils in primary education through the design and implementation of an athletics program.